Implementation of computer applications based on Free Software in Libraries and Units of Information - Herrera Burgos, Rolando (2012)
The libraries and units of information of nowadays play a role of great importance in the diffusion of the human knowledge. They have had to transform to offer new services and to face the fact that the users of nowadays make use of the digital technology to accede to the sources of data without pausing to think about the quality of the obtained data. The union between the library and Free Software is natural since in a fundamental base it looks for that the user has access without you limit and without restrictions.